The Effect of Exercise-Based Pulmonary Rehabilitation on Quality of Life in Recovered COVID-19 Patients; a Quasi-Experimental Study - Rayegani, Seyed Mansoor; Bozorgmehr, Rama; Angooti Oshnari, Leila; Mahdi Kaghazi, Amir Hossein (Archives of Academic Emergency Medicine, 2022)
Introduction: The coronavirus disease 2019 (COVID-19) is associated with a variety of physical and emotional disorders, and subsequently lower Quality of Life (QOL). This study aimed to investigate the effect of a 2-week exercise-based pulmonary rehabilitation on clinical characteristics and QOL of severe COVID-19 patients after discharge from intensive care unit (ICU). Methods: In this quasi-experimental study, eligible severe COVID-19 cases, who had survived and were discharged from ICU were selected using convenience sampling method. O2 saturation (SpO2), pulse rate, dyspnea, and QOL were evaluated and compared before and after two weeks of exercise-based pulmonary rehabilitation (PR). Results: 35 cases with the mean age of 57.86 ± 11.73 (18-75) years were studied (51.4% female). The mean SpO2 increased from 90.41 ± 3.97 to 95.11 ± 1.96% after two weeks of pulmonary rehabilitation (p<0.0001). In addition, the mean pulse rate (98.97±16.23 to 88.91±14.03 pulse/minute; p<0.001) and the mean dyspnea severity (5.6±1.97 to 3.45±1.97; p<0.0001) decreased after two weeks of intervention. Besides, the mean total QOL and its dimensions, including general health (p<0.0001), physical status (p<0.0001), emotional status (p = 0.036), and social function (p<0.0001) of patients, had significantly increased after intervention. Conclusion: Based on the findings of this study, it seems that two-week exercise-based pulmonary rehabilitation could be effective in increasing the SpO2, decreasing dyspnea and pulse rate, and improving the QOL of patients with severe COVID-19 after discharge from ICU.